Phosphine and carbene azido-cations: [(L)N3]+ and [(L)2N3]+. Issue 11 (4th August 2015) - Winkelhaus, Daniel; Holthausen, Michael H.; Dobrovetsky, Roman; Stephan, Douglas W.
Abstract : The cationic N3 -species [( p -HC6 F4 )3 PN3 ] + (1 ) featuring a perfluoro-arene phosphonium group serves as a N3 + -source in stoichiometric reactions with several Lewis bases (L) allowing for the stepwise formation of [(L)N3 ] + and [(L)2 N3 ] + cations (L = phosphine, carbene) with liberation of ( p -HC6 F4 )3 P. Abstract : The cationic N3 -species [( p -HC6 F4 )3 PN3 ] + (1 ) featuring a perfluoro-arene phosphonium group serves as a N3 + -source in stoichiometric reactions with several Lewis bases (L) allowing for the stepwise formation of [(L)N3 ] + and [(L)2 N3 ] + cations (L = phosphine, carbene) with liberation of ( p -HC6 F4 )3 P. X-Ray diffraction analysis and computational studies provide insight into the bonding in these remarkably stable azido-cations.